Physical attractiveness and person perception judgment. - Ocate, Josefina Tanlogon (1997.)
This is an experiment study to examine if the subjects' perception of the stimulus persons' attractiveness and subjects' perception of their own attractiveness influence perception. The independent variables in the study are subjects' perception of stimulus, person's attractiveness and subjects' perception of their own attractiveness. The dependent variable is perception (perceiving positively or negatively). The study hypothesized that subjects perception of their own attractiveness will influence perception of others. The subjects of the study were high school female students of Dapdap National High School, Tigbauan Iloilo for the school year 1996-1997. Attractiveness of stimulus persons' was measured through average ranking given by independent panel of judges. Attractiveness of subjects was measured through the use of Personal Attractiveness Rating Scale. It contained one item which measure attractiveness in a 9-point scale (1+very unattractive to 9=very attractive). Two way Analysis Variance (ANOVA) was performed on the data to determine whether there is a significant difference between groups. The result of the study revealed a significant F value at p< .05 on the subjects perception of stimulus persons' attractiveness to their perception. There is no significant main effect for the subjects perception of their attractiveness to their perception of the stimulus persons. There is no significant interaction between subjects' perception of the stimulus persons' attractiveness and their own perception of self attractiveness to their perception of the stimulus person. It was therefore inferred that subjects; perception of their own attractiveness did not influence their perception of others.
Thesis (Undergraduate, Bachelor of Arts in Psychology-Management) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Perception